2019
DOI: 10.3390/jof5010011
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Candidiasis in Infants and Children: Recent Advances in Epidemiology, Diagnosis, and Treatment

Abstract: This paper reviews recent advances in three selected areas of pediatric invasive candidiasis: epidemiology, diagnosis, and treatment. Although the epidemiological trends of pediatric invasive candidiasis illustrate a declining incidence, this infection still carries a heavy burden of mortality and morbidity that warrants a high index of clinical suspicion, the need for rapid diagnostic systems, and the early initiation of antifungal therapy. The development of non-culture-based technologies, such as the T2Cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 43 publications
1
38
0
2
Order By: Relevance
“…The underlying diseases and risk factors for candidaemia in the various age groups of paediatric patients are different . For instance, as shown in the current study, prematurity, CVC use, mechanical ventilation, broad‐spectrum antibiotic therapy or prophylaxis, receipt of TPN, and long stay at the ICU were the major predisposing factors for neonatal candidaemia, whereas cancer, CVC use, chemotherapy, corticosteroid therapy and antifungal and antibiotic therapy or prophylaxis accounted for most of the candidaemia among infants and children.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The underlying diseases and risk factors for candidaemia in the various age groups of paediatric patients are different . For instance, as shown in the current study, prematurity, CVC use, mechanical ventilation, broad‐spectrum antibiotic therapy or prophylaxis, receipt of TPN, and long stay at the ICU were the major predisposing factors for neonatal candidaemia, whereas cancer, CVC use, chemotherapy, corticosteroid therapy and antifungal and antibiotic therapy or prophylaxis accounted for most of the candidaemia among infants and children.…”
Section: Discussionsupporting
confidence: 84%
“…This indicates that healthcare-associated risk factors are a good predictor of positive blood culture. 6,14,[19][20][21][22][23][24][25] Strikingly, invasive candidiasis caused by non-albicans Candida species has only been reported in the past two decades. 22 Nonalbicans Candida species have emerged as agents of candidaemia, with an overall decreased incidence rate of C. albicans from 70% to 50% in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Data have additionally shown that the epidemiology of candidemia differs significantly among pediatric and adult populations, especially in terms of Candida species distribution, underlying conditions, risk factors and outcomes. [5][6][7][8][9][10][11][12] Most large prospectively designed epidemiology studies have excluded pediatric patients. Therefore, detailed knowledge of the epidemiology of Candida species among pediatric groups is limited.…”
mentioning
confidence: 99%
“…Infections by pathogenic fungi are increasingly recognized as an emerging threat to public health (Wu, 1994; Walsh et al, 1996). These problems are associated with resistance to antibiotics and toxicity during prolonged treatment with several antifungal drugs (Giordani et al, 2001).…”
Section: Discussionmentioning
confidence: 99%